USING A HYBRID APPROACH IN DEVELOPING SOFTWARE FOR MORPHOLOGICAL ANALYSIS OF UZBEK WORDS - Berdiyorov Anvar (Zamonaviy ta’lim va tilshunoslik rivoji, 2026)
This article discusses the use of a hybrid approach in developing software for the morphological analysis of Uzbek words. Uzbek belongs to the agglutinative language family and allows the formation of numerous grammatical word forms, which makes morphological analysis a challenging task. A hybrid model combining rule-based and machine learning approaches is proposed. The advantages, software architecture, and practical applications of the model are analyzed. The results demonstrate that the hybrid approach can improve the accuracy and efficiency of morphological analysis systems.